The US exchange rate behavior: an advanced test on price parity theorem - Syed Mohamed, Mohamed Ariff; Zarei, Alireza (Universiti Putra Malaysia Press, 2014)
We researched a significant topic on exchange rate behavior by restating the test procedures in a novel manner and applying an appropriate econometric methodology to re-examine exchange rate behavior of the US economy. The central research question is: Do inflation differences across two economies fully account for exchange rate changes, if controls for non-parity factors are embedded while controlling for interest rate differences? The results affirm, for the first time, that price parity factor holds well while other factors - interest rates and non-parity factors - also affect exchange rates significantly. Our tests also identifies the time to equilibrium to be 0.139 (13.9%) per quarter to adjust to equilibrium value. In our view, these findings extend our knowledge of how the US dollar behavior is consistent with parity and non-parity theorems. Prior tests have been inconclusive on parity factors. The Malaysian Ringgit is heavily dependent on the US dollar exchange rate, and our findings thus have monetary policy implications for the Malaysia's regulators.